VALIDASI METODE PENGUJIAN VISKOSITAS MU01/VIS/2011 DI LABORATORIUM TERPADU DENGAN MENGGUNAKAN VISKOMETER BROOKFIELD - Agung Nugroho (UIN Sunan Kalijaga Yogyakarta, 2016)
Integrated Laboratory UIN Sunan Kalijaga Yogyakarta is a testing laboratory accredited by the National Accreditation Committee (KAN) with number LP-635 IDN. One parameter is the viscosity testing. Integrated Laboratory UIN Sunan Kalijaga Yogyakarta implementing viscosity test method MU01 / VIS / 2011. This test method validation necessary in order to have the valid test results. Validation is conducted every year to obtain a quality assurance test results. Validation carried out because the test method developed by the laboratory. Validation is done by measuring the level of precision and accuracy using standard materials. Measurement of standard materials does as much as 12 times the measurement. From the measurement results obtained at the price of precision is under 0.05% and accuracy between 99 % -100 %. In the test method validation can be concluded that the test method MU01 / VIS / 2011 fit for use as a test method. Validation testing methods viscometer above, still meet the requirements at a price of precision and accuracy.